FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI PADA PERUSAHAAN PEFINDO25 - Tegar Dwi Pamungkas; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research was conducted to examine the influence of Financial Distress, Litigation Risk, Company Sizeon Accounting Conservatism in Indonesian Pefindo25 companies listed on the Indonesia Stock Exchangefrom 2016 to 2021. The research sample used was 25 Pefindo25 companies. The sampling technique usedwas purposive sampling. The analysis method used is Moderated Regression Analysis (MRA). Based on theresults of the t test, it shows that Financial Distress, Litigation Risk has an effect on AccountingConservatism and. Company size can moderate the influence of financial distress on accountingconservatism. Company size can moderate the influence of litigation risk on accounting conservatism. Atthe Pefindo25 company on the Indonesian Stock Exchange